Neurodevelopmental and Growth Outcomes Among Low-Birth-Weight Infants Receiving Early Kangaroo Mother Care: A Cross-Sectional Study - Chowdhury, Mahmudul Hoque; Islam, Thrina (Journal of Rangpur Medical College, 2026)
Background: Infants with low-birth-weight face heightened risks of mortality, growth retardation, and neurodevelopmental deficits, especially in resource-limited environments. Kangaroo Mother Care (KMC) enhances survival and growth. However, data concerning its long-term neurodevelopmental effects in Bangladesh is still insufficient. Objective: To evaluate neurodevelopmental and growth outcomes in low-birth-weight children receiving early Kangaroo Mother Care and to identify predictors of developmental delay. Methods: This cross-sectional analytical study was conducted at Bangladesh Shishu Hospital & amp; Institute, Dhaka from June 2023 to November 2023, involving 65 low-birth-weight children aged 12 to 36 months who received early Kangaroo Mother Care there. The ASQ-3 was used to look at neurodevelopment, and WHO standards were used to look at anthropometric measurements. Chi-square tests, independent t-tests, pearson correlation, and multivariable logistic regression were used to identify predictors of developmental delay. Results: In general, 67.9% of children demonstrated age-appropriate growth across all areas, with early initiation of Kangaroo Mother Care within 24 hours (AOR=0.38, p=0.026) and daily practice exceeding eight hours (AOR=0.41, p=0.045) serving as protective factors. A longer duration of KMC was positively associated with elevated ASQ-3 scores (r=0.18–0.29, p<0.05). Children with delays had much lower anthropometric measurements. Conclusion: Early and continuous Kangaroo Mother Care enhances neurodevelopment and growth in low-birth-weight children, underscoring its significance in conjunction with nurturing home environments in resource-constrained contexts. J Rang Med Col.2026 Mar;11(1): 183-188